2022 EDUCAUSE Horizon Report® Data and Analytics Edition - Reinitz, Betsy Tippens; McCormack, Mark; Reeves, Jamie; Robert, Jenay; Arbino, Nichole; Anderson, Jeremy; Hamman, John; Johnson, Connie; Kew-Fickus, Olivia; Snyder, Rob; Stevens, Mary (EDUCAUSE, 2022)
With the 2022 data and analytics edition, we further expand our series of Horizon Reports to focus on an emerging area of practice that is driving institutional decision-making and strategic planning for the future—the trends, technologies, and practices that are shaping the world of postsecondary data and analytics. Based on a methodology that grounds the findings in the perspectives and expertise of a panel of leaders in higher education data and analytics, in this report we summarize the panel's input on the major trends shaping higher education, including panelists' reflections on the implications of this research for the future of higher education for particular institutional roles.
Keywords: Artificial Intelligence (AI); CIO; Data Administration and Management; Data Curation; Analytics; Business Intelligence (BI)